Productivity and Innovation in the Czech Republic A Firm-Level Perspective - Davies, Elwyn (World Bank E-Library Archive, 2019)
Convergence of productivity of Czech firms towards peer countries is slow, especially for smaller firms. Czech labor productivity was 68.3 of that in Germany and the productivity gap is in particular large for micro, small and medium enterprises (MSMEs). MSMEs (defined as having less than 250 employees) form the backbone of the Czech economy, accounting for 67.3percent of total employment and 55.2 percent of value added (at factor cost) but face weak innovation demand and an unfavorable position in global value chains. The Czech Ministry of Industry and Trade (MIT) is developing a new Small and Medium Enterprise (SME) Strategy and Implementation Plan for the period 2021-202no7 to boost firm productivity and competitiveness of domestic SMEs. MIT has requested support from the European Commission under Regulation (EU) 2017/825 on the establishment of the Structural Reform Support Programme ("SRSP Regulation"). The request has been analyzed by the European Commission in accordance with the criteria and principles referred to in Article 7(2) of the SRSP Regulation, following which the European Commission has agreed to provide technical support to the Czech Republic, together with the World Bank, to conduct analytical work on the status of SMEs